Strategi Guru Mengatasi Perundungan di SMA Negeri 2 Polewali - Abd Basit; Fatimah Azis (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2024)
This scientific article discusses the roles and strategies that can be used by teachers in dealing with bullying at SMA Negeri 2 Polewali. Bullying among students has a serious impact on academic performance, emotional well-being, and the learning environment in schools. This research aims to document concrete strategies that can be implemented by teachers as an effort to overcome bullying.This research method involved collecting data through surveys, interviews and observations of teachers at SMA Negeri 2 Polewali. Data analysis revealed that teachers play a crucial role in identifying, preventing, and addressing bullying. This article discusses specific strategies that can be implemented by teachers, including implementing pedagogical approaches that promote inclusivity, active involvement in monitoring student activities, and implementing empathy and social skills development programs.